Environmental initiatives of SMEs in Malaysia:an investigation of reporting practice and motivations / Nik Zam Nik Wan (Institute of Graduate Studies, UiTM, 2017)
SMEs are considered as the backbone of most economic growth worldwide including Malaysia but their existence and importance as individual are frequently under estimated. SME’s individual environmental impacts seem to appear at a minimum level but environmental cases reported otherwise. Even though they should be equally accountable, little is known about SMEs’ initiatives in preserving the environment. Inspired by the above, this study decided to explore Malaysian SMEs’ involvement in environmental initiatives including environmental reporting. The motivations for environmental initiatives of SMEs in Malaysia are investigated to provide opportunities to encourage and to educate more SMEs to implement the environmental initiatives and communicate their environmental information. This study used qualitative research methodology employing grounded theory approach. The data collection process included semi-structure interviews, content analysis of documents and observations and focused only on SMEs that are registered as members of FMM. Through interviews, observations and content analysis this study revealed that the SMEs did implement some environmental initiatives. Despite being said to be smaller in nature findings of this study indicated that Malaysian SMEs also demonstrated their responsibility towards the environment. These SMEs not only complied with the related environmental rules and regulations but they also committed their limited financial resources to implement several environmental initiatives. Among the non-mandatory initiatives implemented are environmental management system, waste management, energy conservations, tree planting and creating environmental awareness…